Randomized controlled trial comparing outcome of intramedullary nailing versus percutaneous locked plating of extra-articular proximal tibial fractures - Chaudhary, Pashupati; Shrestha, B P; Khanal, G K; Rijal, R; Maharjan, R (Health Renaissance, 2017)
Background: Extra-articular fracture of proximal tibia is one of common injury.The study is randomized controlled trial in which individuals sustaining a fracture of the proximal metaphysis of the tibia will be operatively managed by one of two strategies. The first strategy involves fixation of the fracture with a reamed, interlocking intramedullary nail (Nail Group). The second treatment strategy involves percutaneous fixation of the fracture with a locking plate (Plate Group).Objective: To compare the functional outcome of intramedullary nailing versus percutaneous locked plating of extra-articular proximal tibial fractures in adults in terms of procedure time, time to achieve union, functional outcome, blood loss, cost of treatment, complication if any. Methods: It is randomised controlled trial study. The patients were randomized into two groups, each of size 60: Group A (IMIL group) Group B (Locking Plate group). During procedure patients were evaluated for blood loss, procedure time or any complications. Immediate post operative complications were taken into account and post operative radiological parameters measured.Results: A total of 120 patients (75 male and 45 female) were included in the study. Fifty five patients were less than 25 years age group followed by 30 patients between 25-40 yrs, 25 patients less than 25 age group and 10 patients more than 55 years. The average blood loss is 95 ml in IMIL group and 105 ml in locked plate group.Conclusion: IMIL is more expensive than percutaneous locked plates IMIL came out as a shorter surgery with little blood loss however at the same time much costlier to locked plating. Health Renaissance 2015;13 (3):